Immobilization of cellulase enzyme onto iron oxide nanoparticles to improve thermal and pH stability - A. H., Mustafa; S. S., Rashid; B. H., Sikder; A. A., Sasi; M. H., Rahim (2021)
Lignocellulosic enzymes have been used in the pretreatment and hydrolysis of the biomass, are getting special attention to produce the sustainable green biofuel. However, free enzymes not only difficult to separate from reaction media but also highly temperature and pH sensitive, so a controlled environment is required to maintain. A proper immobilization support material needs to adopt to improve their stability and reusability. In this research, cellulase immobilized magnetic nanoparticles were prepared to improve thermal and pH stability and reusability of enzyme.